Programming and execution models for parallel bounded exhaustive testing - Awar, Nader Al; Jain, Kush; Rossbach, Christopher J.; Gligoric, Milos (Proceedings of ACM on programming languages, 2021)
Bounded-exhaustive testing (BET), which exercises a program under test for all inputs up to some bounds, is an effective method for detecting software bugs. Systematic property-based testing is a BET approach where developers write test generation programs that describe properties of test inputs. Hybrid test generation programs offer the most expressive way to write desired properties by freely combining declarative filters and imperative generators. However, exploring hybrid test generation programs, to obtain test inputs, is both computationally demanding and challenging to parallelize. We present the first programming and execution models, dubbed Tempo, for parallel exploration of hybrid test generation programs. We describe two different strategies for mapping the computation to parallel hardware and implement them both for GPUs and CPUs. We evaluated Tempo by generating instances of various data structures commonly used for benchmarking in the BET domain. Additionally, we generated CUDA programs to stress test CUDA compilers, finding four bugs confirmed by the developers.